Dramatic response of iris and retinal neovascularisation following usage of intravitreal ranibizumab as pre-operative adjunct in vitrectomy for advanced proliferative diabetic retinopathy - Malisa A; Mae-Lynn CB (Department of Surgery, UKM Medical Centre, 2011)
A 37-year-old Malay woman presented with progressive deterioration in vision and was diagnosed with advanced proliferative diabetic retinopathy with neovascular glaucoma. Intravitreal ranibizumab injection (an anti-vascular endothelial growth factor) was administered prior to vitrectomy. Slit lamp assessment 2 days post-injection revealed significant regression of both iris and retinal neovascularisation. This resulted in adequate reduction of intra-ocular pressure prior to surgery. In addition, the regression of retinal vessels reduced the risk of intra-operative haemorrhage, thus aiding the surgical excision of the fibrovascular membranes. Periodic post-operative assessment in the first 3 weeks showed minimal inflammation and no recurrence of vitreous haemorrhage. This case illustrates that intravitreal ranibizumab has a role as an adjunct therapy prior to diabetic vitrectomy to significantly reduce the risk of intra-ocular haemorrhage.